Locked-in Syndrome: Insights into Etiology, Diagnosis, Management, and Quality of Life - Urszula Zelik; Wojciech Florczak; Joanna Śnieżna; Jakub Dziewic; Karol Dzwonnik; Wiktoria Domino; Gabriela Trestka; Maria Przygoda; Jagienka Włodyka; Kamila Stępień; Sabina Adamczyk (Quality in Sport)
Locked-in Syndrome (LIS) is a rare and severe neurological condition resulting from damage to the ventral pons, leading to complete paralysis of voluntary muscles while preserving consciousness and cognitive function. This review consolidates current knowledge on the etiology, diagnosis, management, and quality of life in LIS, emphasizing its complexity and the need for a multidisciplinary approach.The condition’s etiological spectrum includes vascular events, trauma, infections, and demyelinating disorders, necessitating a comprehensive diagnostic approach integrating advanced neuroimaging and electrophysiological tools.